Impoverishment of induced displacement and resettlement (DIDR) slum eviction development in Jakarta Indonesia. Issue 3 (2nd September 2018) - Ichwatus Sholihah, Puput; Shaojun, Chen
ABSTRACT: The Government of DKI Jakarta plans to free the city from slum dwellings by 2020. In the quest to mitigate floods from Jakarta, the government relocated about 25, 533 people; 5, 725 households and 5, 379 business units from 12 slum areas between 2014 and 2016. With the intention of moving slum dwellers from a highly congested and poor environment to a more decent one, this policy looks like one that helps the poor earn a better life, at first glance. Nevertheless, this policy is still considered ineffective because it results in the impoverishment of most of the displaced population. This study attempts to analyze the risk of impoverishment resulting from displacement and resettlement using the IRR model and also append another factor that emerged as a risk-specified relocation development and resettlement program of slums in Jakarta Indonesia.